Water-soluble allyl sulfones for dual site-specific labelling of proteins and cyclic peptides. Issue 5 (11th February 2016) - Wang, Tao; Riegger, Andreas; Lamla, Markus; Wiese, Sebastian; Oeckl, Patrick; Otto, Markus; Wu, Yuzhou; Fischer, Stephan; Barth, Holger; Kuan, Seah Ling; Weil, Tanja
Abstract : Allyl sulfones as efficient disulfide rebridging agents for site-specific protein modifications with up to two additional functionalities in water. Abstract : Water-soluble allyl sulfones provide convenient site-specific disulfide rebridging of native proteins and cyclic peptides. The site-selective functionalization of (a) the peptide hormone somatostatin, (b) the interchain disulfide of bovine insulin and (c) functionalization of the proteins GFP and lysozyme with allyl sulfones proceeds in aqueous solution. Allyl sulfones offer three functionalizable sites that react with thiol containing molecules in a step-wise fashion. Dual labeling of proteins and cyclic peptides is achieved i.e. the attachment of a chromophore and an affinity tag in a single reaction step, which is of great significance for the construction of precise multifunctional peptide and protein conjugates.